Functional beverage instant ginger powder (zingiber officinale) with addition of betel extraction (piper bettle). Issue 1 (May 2020) - Arifan, F; Winarni, S; Wahyuningsih,; Pudjihastuti, I; Wisnu Broto, R T D
Abstract: Ginger is one of the herbal plant species that is used as cook seasoning because it can add a distinctive flavor to foods. Ginger also has so many substance contents that is needed for the human body, such as essential oil (0, 5-5, 6%), zingiberon, zingeberin, zingibetol, barneol, kamfer, folandren, sineol, gingerin, vitamin (A, B1, and C), carbohydrate (20-60%), resin and organic acid. This research aims to find the value of antioxidant and quality requirements of traditional beverage powder from ginger powder. The tools which are used in the making of ginger powder with the addition of betel leaf extract are: knife, pan, filter, blender, stove, and spatula. While the tools for analyzing are beaker glass, measuring cylinder, test tube, measuring flask, oven, petri dish, Erlenmeyer. The ingredients which are used in the making of ginger powder are : ginger, betel leaf, sugar and water. The result of this research found that water contain of instant ginger betel is 2, 080% while ash content of instant ginger betel is 0, 533%. This research also analyzes the level of metal contamination, where the metal that is tested is Pb, Cu and Zn metal. The result of the Cu metal contamination is equal to 0, 198 ppm, Zn metal is 0, 527 ppm, while the Pb metal contamination is undetected. The research is also analyzing the content of antioxidant and found that the content of antioxidant is 41, 632%. The conclusion is the content of metal contamination is Cu, Zn and Pb, while water content and ash content is still the same with SNI 01-4320-1996.